Menghubungkan Jaringan UMKM dan Implikaisnya terhadap Pengembangan Wilayah - Lucas Magelhaes; Arif Dwi Hartanto (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2018)
This paper seeks to show that network studies on MSMEs can enrich the analysis of regional development policies. However, MSMEs have proven to have an important role in the economy. While the network has been recognized as a third form of organization, namely between markets and hierarchies that occupy a key role in many discussions about the process of regional development. Therefore, the exploration conducted in this paper is to examine the main features of the importance of UMKM network to see three aspects, namely: (i) institutional and entrepreneurial processes (ii) regional distribution; and (iii) regional innovation systems. These three aspects will be explored how the implications for regional development. The results of this paper can help in identifying some of the components that can be used to build development policies and regional competitiveness based on the advantages of special features on the existence of UMKM networks.